Wear-resistant coating modified injection mold and preparation process thereof
By coating the bottom and surface resin coatings on the surface of the injection mold successively to form a cross-linked structure, the problem of easy corrosion and wear in the injection mold during use is solved, good wear resistance and impact resistance are achieved, and the use of the mold is extended life.
Patent Information
- Application Number
- CN202411623194.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-11-14
AI Technical Summary
Injection molds are susceptible to corrosion and wear during use, resulting in the impact of precise dimensions and a decrease in yield. The existing technology is difficult to effectively solve this problem.
Using an injection mold with wear-resistant coating modification and its preparation process, two different resin coatings are sequentially coated on the surface of the mold to form a bottom coating and a top coating. The base coating uses 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether as raw materials, and the addition reaction is carried out through silicon hydrogen bonds and carbon carbon double bonds to obtain acrylic acid-modified silicon-containing Resin. The surface coating uses perfluoropolyether glycol and isophorone diisocyanate as raw materials, and isoprone diisocyanate is epoxy-based end capping treatment to form an epoxy-based end capping fluoro-containing polyurethane prepolymer and intersect with epoxy resin E51. Coupled reaction.
The wear-resistant coating prepared by this process has good protective effect, which can significantly improve the wear resistance and impact resistance of the injection mold, extend the service life of the mold, and maintain the flowability of the plastic melt.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of wear-resistant coatings, in particular to an injection mold modified with a wear-resistant coating and a preparation process thereof. Background Art
[0002] Injection molds are commonly used tools in the production of plastic products, and they also give plastic products a complete structural form. The general production process is to inject the heated and melted plastic into the mold cavity under high pressure through the injection molding machine, and then obtain the molded product after cooling and solidification.
[0003] With the development of injection mold processing technology, its structure has become more and more complex. With the continuous emergence of new plastic raw materials, more and more plastic materials have caused great corrosion and wear to the mold. Since injection molding is a processing method used in mass production of certain parts with complex shapes, when the injection mold is corroded and worn, its precise size will be affected, which will lead to a decrease in the yield rate. The solution is to choose a suitable coating to protect the injection mold and ensure the fluidity of the plastic melt in the injection mold. Therefore, it is very necessary to develop an injection mold modified with a wear-resistant coating. Summary of the invention
[0004] The object of the present invention is to provide an injection mold modified with a wear-resistant coating and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: an injection mold modified with a wear-resistant coating and a preparation process thereof, comprising the following steps:
[0006] Step 1:
[0007] S11: Mix 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether, heat the system to 50-60°C, stir for 5-10 minutes, add KARSTEDT catalyst, stir until the temperature stabilizes, and continue the reaction for 3-5 hours to obtain tetraepoxysiloxane;
[0008] S12: taking tetraepoxysiloxane and heating it to 85-95° C., mixing α-methylacrylic acid, catalyst benzyltriethylammonium chloride, and inhibitor p-hydroxyanisole, and then dripping them into the tetraepoxysiloxane, and controlling the dripping of the mixture to be completed within 30-60 minutes; after the addition, heating it to 100-110° C. and reacting for 2-3 hours to obtain an acrylic modified silicone resin;
[0009] Step 2:
[0010] S21: adding boron nitride to isopropanol to obtain a suspension having a concentration of 1 to 3 g / L, ultrasonically oscillating at a power of 200 to 300 W for 24 hours, centrifuging at 3000 to 4000 r / min for 10 to 15 minutes, taking the upper suspension, and centrifuging at 8000 to 10000 r / min for 10 to 15 minutes, taking the upper clear liquid, and air-drying to obtain exfoliated boron nitride;
[0011] S22: Disperse the exfoliated boron nitride in deionized water, adjust the pH to 8-8.5 with tris(hydroxymethyl)aminomethane, add ethyl orthosilicate to hydrolyze for 6 hours and then age for 1-2 hours, add 3-mercaptopropyltrimethoxysilane, stir the reaction for 3-4 hours and filter, wash the filtrate with deionized water and ethanol for 3-5 times respectively, to obtain silica-modified boron nitride powder;
[0012] Step 3:
[0013] S31: mixing perfluoropolyether diol and isophorone diisocyanate, using dibutyltin dilaurate as a catalyst, heating to 70-80° C. for reaction for 2-4 hours, and cooling to obtain a polyurethane prepolymer;
[0014] S32: adding glycidol to the polyurethane prepolymer at 40-50° C., using dibutyltin dilaurate as a catalyst, and reacting at 70-80° C. for 1-2 hours to obtain an epoxy-terminated fluorine-containing polyurethane prepolymer;
[0015] Step 4:
[0016] S41: Select an injection mold made of aluminum alloy, vertically cross-grind the surface of the injection mold with sandpaper for 5 minutes, clean the surface with clean water, and then soak the injection mold in hydrochloric acid solution and sodium hydroxide solution for 3 minutes in sequence; clean with acetone to remove surface impurities, mix silane coupling agent KH550, ethanol, and deionized water and apply it to the surface of the injection mold, and then dry it at 100-120° C. for 1-2 hours to obtain a pretreated injection mold;
[0017] S42: Mix acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder and acetone, and apply it on the surface of the pretreated injection mold at 20-30 mW / cm 2 After UV curing for 30 to 90 seconds, the coating is dried by air blast at 50 to 60° C. to obtain a base coating with a thickness of 300 to 500 μm;
[0018] S43: epoxy-terminated fluorinated polyurethane prepolymer, epoxy resin E51, curing agent, defoaming agent and epoxy diluent are mixed and coated on the base coating, and cured at 100-120° C. for 1-2 hours to obtain a surface coating with a thickness of 100-200 μm.
[0019] Furthermore, in S11, the molar ratio of 2,4,6,8-tetramethylcyclotetrasiloxane to allyl glycidyl ether is 1:4.
[0020] Furthermore, in S12, tetraepoxysiloxane and α-methacrylic acid are reacted at a molar ratio of epoxy group to carboxyl group of 2:1.
[0021] Furthermore, in S22, the amount of each component used, by weight, is 3 to 5 parts of exfoliated boron nitride dispersion, 2.5 to 3 parts of ethyl orthosilicate, and 0.2 to 0.28 parts of 3-mercaptopropyltrimethoxysilane.
[0022] Furthermore, in S31, perfluoropolyether diol and isophorone diisocyanate are mixed at a molar ratio of hydroxyl group to isocyanate group of 2:1.
[0023] Further, in S32, glycidol is added to the polyurethane prepolymer at a molar ratio of hydroxyl group to isocyanate group of 1:1.
[0024] Furthermore, in S41, the concentration of the hydrochloric acid solution is 0.2-0.25 mol / L, and the concentration of the sodium hydroxide solution is 0.2-0.25 mol / L.
[0025] Furthermore, in S41, the weight ratio of silane coupling agent KH550, ethanol and deionized water is 20:(70-75):(5-10).
[0026] Furthermore, in S42, acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone are mixed in a weight ratio of (100-120):(3-5):(46-54):(3-8):100.
[0027] Furthermore, in S43, the amount of each component, by weight, is 20 to 30 parts of epoxy-terminated fluorine-containing polyurethane prepolymer, 70 to 80 parts of epoxy resin E51, 35 to 40 parts of curing agent, 8 to 13 parts of defoaming agent, and 10 to 15 parts of epoxy diluent.
[0028] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: the present invention provides an injection mold modified with a wear-resistant coating and a preparation process thereof. After the surface of the injection mold is pretreated, two different resin coatings are sequentially coated on the surface of the mold to form a bottom coating and a top coating, respectively. The bottom coating has a strong bonding force with the mold surface and can form a cross-link with the top coating after thermal curing, so it has a good protective effect on the injection mold.
[0029] Specifically, in the present invention, the bottom coating is made of 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether as raw materials, and an addition reaction is carried out through a silicon-hydrogen bond and a carbon-carbon double bond to obtain a tetraepoxysiloxane, and then the tetraepoxysiloxane and α-methacrylic acid are subjected to an esterification reaction to introduce a carbon-carbon double bond to obtain an acrylic modified silicon-containing resin. In order to give the coating good wear resistance, the present invention loads silicon dioxide as an inorganic filler on the surface of boron nitride by a precipitation method, and uses 3-mercaptopropyltrimethoxysilane to modify and introduce a mercapto group. Under the action of a photoinitiator, the acrylic modified silicon-containing resin undergoes self-polymerization, and can react with the mercapto group on the surface of the filler to form a bottom coating on the surface of the mold. The introduction of inorganic fillers improves the wear resistance of the coating, and the silicon-oxygen bonds in the coating also have strong flexibility and heat resistance, which improves the shortcomings of conventional vinyl resins having large volume shrinkage, easy cracking, and poor high temperature resistance during polymerization.
[0030] The present invention uses perfluoropolyether diol and isophorone diisocyanate as raw materials, reacts to prepare polyurethane prepolymer, and uses glycidol for end-capping to obtain epoxy-terminated fluorine-containing polyurethane prepolymer; the epoxy-terminated fluorine-containing polyurethane prepolymer is mixed with epoxy resin E51, coated on the surface of the bottom coating, and heated to form a surface coating. In the temperature-raising and curing stage, the epoxy-terminated fluorine-containing polyurethane prepolymer and the epoxy resin can be chemically cross-linked through the epoxy group, and the epoxy group in the bottom coating can also be self-cross-linked at high temperature and react with the epoxy group in the surface coating. Thermal curing not only improves the bonding performance between the bottom coating and the surface coating, but also greatly improves the problem of poor bonding performance of conventional vinyl resins, and the bonding performance of the bottom coating and the injection mold is enhanced.
[0031] The bottom coating of the present invention contains silicon oxygen bonds, and the surface coating contains organic carbon fluorine bonds. By coating separately and then polymerizing, the phase separation after the different molecular segments with poor compatibility are avoided. In the wear-resistant coating, the organic fluorine in the surface coating has low surface energy and high strength, which can ensure the fluidity of the plastic melt in the injection mold during use and facilitate demolding; while the organic silicon segment in the bottom coating is soft and tough, which can reduce the internal stress of the coating when impacted by external force and avoid cracking. After curing, the two complement each other and improve the performance of the coating. In addition, it is necessary to add that when preparing acrylic modified silicone resin, in order to avoid the complete reaction of epoxy groups, the present invention controls the esterification rate to 50%, that is, tetraepoxysiloxane and α-methyl acrylic acid are reacted at a molar ratio of epoxy and carboxyl groups of 2:1, and the prepared acrylic modified silicone resin can be photothermally cured, thereby achieving the effect to be achieved by the present invention. DETAILED DESCRIPTION
[0032] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0033] Materials used in the present invention and their sources: perfluoropolyether diol (Mn=2000) comes from Fuzhou Taipuda New Materials Co., Ltd.; boron nitride comes from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd., item number 102414; photoinitiator 2959 comes from Nanjing Milan Chemical Co., Ltd.; epoxy resin E51 comes from Hebei Linyuan Fine Chemical Co., Ltd.; curing agent is a polyetheramine modified curing agent, from Suzhou Hengst Industrial Co., Ltd., item number 4026; defoaming agent comes from Jiangsu Tengda Additive Co., Ltd., item number T-118; epoxy diluent comes from Guangzhou Wei Chuang High-tech Materials Technology Co., Ltd., item number WE-6690.
[0034] Embodiment 1: A wear-resistant coating modified injection mold and a preparation process thereof, comprising the following steps:
[0035] Step 1:
[0036] S11: Mix 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether in a molar ratio of 1:4, heat the system to 50°C, stir for 5 minutes, add KARSTEDT catalyst, stir until the temperature stabilizes, and continue the reaction for 3 hours to obtain tetraepoxysiloxane;
[0037] S12: Take tetraepoxysiloxane and heat it to 85°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride, and inhibitor p-hydroxyanisole, and add them dropwise to the tetraepoxysiloxane, and control the mixture to be added dropwise within 30 minutes; after the addition, heat it to 100°C and react for 2 hours to obtain an acrylic acid-modified silicone-containing resin; wherein the tetraepoxysiloxane and α-methylacrylic acid react at a molar ratio of epoxy group to carboxyl group of 2:1;
[0038] Step 2:
[0039] S21: Add boron nitride to isopropanol to obtain a suspension with a concentration of 3 g / L, ultrasonically oscillate at a power of 200 W for 24 hours, centrifuge at 3000 r / min for 10 minutes, take the upper suspension, centrifuge at 8000 r / min for 10 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride;
[0040] S22: 5 g of exfoliated boron nitride was dispersed in deionized water, and the pH was adjusted to 8 using tris(hydroxymethyl)aminomethane, 3 g of ethyl orthosilicate was added for hydrolysis for 6 h and then aged for 1 h, and 0.25 g of 3-mercaptopropyltrimethoxysilane was added; the mixture was stirred for reaction for 3 h and then filtered, and the filtrate was washed with deionized water and ethanol for 3 times respectively to obtain silica-modified boron nitride powder;
[0041] Step 3:
[0042] S31: perfluoropolyether diol and isophorone diisocyanate are mixed in a molar ratio of hydroxyl group to isocyanate group of 2:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70° C. for reaction for 2 h, and the mixture is cooled to obtain a polyurethane prepolymer;
[0043] S32: at 40°C, glycidol was added to the polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 70°C for 1 hour to obtain an epoxy-terminated fluorinated polyurethane prepolymer;
[0044] Step 4:
[0045] S41: Select an injection mold made of aluminum alloy, vertically cross-grind the surface of the injection mold with sandpaper for 5 minutes, clean the surface with clean water, and then soak the injection mold in a 0.2 mol / L hydrochloric acid solution and a 0.2 mol / L sodium hydroxide solution for 3 minutes in sequence; clean with acetone to remove surface impurities, mix silane coupling agent KH550, ethanol, and deionized water in a weight ratio of 20:72:8, and apply the mixture to the surface of the injection mold, and then dry at 100° C. for 1 hour to obtain a pretreated injection mold;
[0046] S42: acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone were mixed in a weight ratio of 100:3:50:3:100 and coated on the surface of the pretreated injection mold at 20 mW / cm 2 After UV curing for 30 seconds, the base coating with a thickness of 500 μm was obtained by air drying at 50°C;
[0047] S43: 20 g of epoxy-terminated fluorinated polyurethane prepolymer, 80 g of epoxy resin E51, 38 g of curing agent, 10 g of defoaming agent, and 13 g of epoxy diluent were mixed and coated on the base coating, and cured at 100° C. for 1 h to obtain a surface coating with a thickness of 100 μm.
[0048] Embodiment 2: A wear-resistant coating modified injection mold and a preparation process thereof, comprising the following steps:
[0049] Step 1:
[0050] S11: Mix 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether in a molar ratio of 1:4, heat the system to 55°C, stir for 8 minutes, add KARSTEDT catalyst, stir until the temperature stabilizes, and continue the reaction for 4 hours to obtain tetraepoxysiloxane;
[0051] S12: Take tetraepoxysiloxane and heat it to 90°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride, and inhibitor p-hydroxyanisole, and add them dropwise to the tetraepoxysiloxane, and control the mixture to be added dropwise within 45 minutes; after the addition, heat it to 105°C and react for 2.5 hours to obtain an acrylic modified silicone resin; wherein the tetraepoxysiloxane and α-methylacrylic acid react at a molar ratio of epoxy group to carboxyl group of 2:1;
[0052] Step 2:
[0053] S21: Add boron nitride to isopropanol to obtain a suspension with a concentration of 3 g / L, ultrasonically oscillate at a power of 250 W for 24 hours, centrifuge at 3500 r / min for 13 minutes, take the upper suspension, centrifuge at 9000 r / min for 12 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride;
[0054] S22: 5 g of exfoliated boron nitride was dispersed in deionized water, and the pH was adjusted to 8.5 using tris(hydroxymethyl)aminomethane, 3 g of ethyl orthosilicate was added for hydrolysis for 6 h and then aged for 2 h, and 0.25 g of 3-mercaptopropyltrimethoxysilane was added; the mixture was stirred for reaction for 3.5 h and filtered, and the filtrate was washed with deionized water and ethanol for 3 times respectively to obtain silica-modified boron nitride powder;
[0055] Step 3:
[0056] S31: perfluoropolyether diol and isophorone diisocyanate are mixed in a molar ratio of hydroxyl group to isocyanate group of 2:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 75° C. for reaction for 3 hours, and the mixture is cooled to obtain a polyurethane prepolymer;
[0057] S32: at 45° C., glycidol was added to the polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 75° C. for 1.5 h to obtain an epoxy-terminated fluorinated polyurethane prepolymer;
[0058] Step 4:
[0059] S41: Select an injection mold made of aluminum alloy, vertically cross-grind the surface of the injection mold with sandpaper for 5 minutes, clean the surface with clean water, and then soak the injection mold in a 0.2 mol / L hydrochloric acid solution and a 0.2 mol / L sodium hydroxide solution for 3 minutes in sequence; clean with acetone to remove surface impurities, mix silane coupling agent KH550, ethanol, and deionized water in a weight ratio of 20:72:8, and apply the mixture to the surface of the injection mold, and then dry at 110° C. for 1.5 hours to obtain a pretreated injection mold;
[0060] S42: acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone were mixed in a weight ratio of 100:3:50:5:100, and coated on the surface of the pretreated injection mold at 25 mW / cm 2 After UV curing for 60 seconds, the base coating with a thickness of 500 μm was obtained by air drying at 55°C;
[0061] S43: 25 g of epoxy-terminated fluorinated polyurethane prepolymer, 75 g of epoxy resin E51, 38 g of curing agent, 10 g of defoaming agent, and 13 g of epoxy diluent were mixed and coated on the base coating, and cured at 105° C. for 1.5 h to obtain a surface coating with a thickness of 100 μm.
[0062] Embodiment 3: A wear-resistant coating modified injection mold and a preparation process thereof, comprising the following steps:
[0063] Step 1:
[0064] S11: Mix 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether in a molar ratio of 1:4, heat the system to 60°C, stir for 10 minutes, add KARSTEDT catalyst, stir until the temperature stabilizes, and continue the reaction for 5 hours to obtain tetraepoxysiloxane;
[0065] S12: Take tetraepoxysiloxane and heat it to 95°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride, and inhibitor p-hydroxyanisole, and add them dropwise to the tetraepoxysiloxane, and control the mixture to be added dropwise within 60 minutes; after the addition, heat it to 110°C and react for 3 hours to obtain an acrylic modified silicone resin; wherein the tetraepoxysiloxane and α-methylacrylic acid react at a molar ratio of epoxy group to carboxyl group of 2:1;
[0066] Step 2:
[0067] S21: Add boron nitride to isopropanol to obtain a suspension with a concentration of 3 g / L, ultrasonically oscillate at a power of 300 W for 24 hours, centrifuge at 4000 r / min for 15 minutes, take the upper suspension, centrifuge at 10000 r / min for 15 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride;
[0068] S22: 5 g of exfoliated boron nitride was dispersed in deionized water, and the pH was adjusted to 8.5 using tris(hydroxymethyl)aminomethane, 3 g of ethyl orthosilicate was added for hydrolysis for 6 h and then aged for 3 h, and 0.25 g of 3-mercaptopropyltrimethoxysilane was added; the mixture was stirred for reaction for 4 h and then filtered, and the filtrate was washed with deionized water and ethanol for 3 times respectively to obtain silica-modified boron nitride powder;
[0069] Step 3:
[0070] S31: perfluoropolyether diol and isophorone diisocyanate are mixed in a molar ratio of hydroxyl group to isocyanate group of 2:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 80° C. for reaction for 4 hours, and the mixture is cooled to obtain a polyurethane prepolymer;
[0071] S32: adding glycidol to a polyurethane prepolymer at a molar ratio of hydroxyl group to isocyanate group of 1:1 at 50°C, using dibutyltin dilaurate as a catalyst, and reacting at 80°C for 2h to obtain an epoxy-terminated fluorinated polyurethane prepolymer;
[0072] Step 4:
[0073] S41: Select an injection mold made of aluminum alloy, vertically cross-grind the surface of the injection mold with sandpaper for 5 minutes, clean the surface with clean water, and then soak the injection mold in a 0.2 mol / L hydrochloric acid solution and a 0.2 mol / L sodium hydroxide solution for 3 minutes in sequence; clean with acetone to remove surface impurities, mix silane coupling agent KH550, ethanol, and deionized water in a weight ratio of 20:72:8, and apply the mixture to the surface of the injection mold, and then dry at 120° C. for 2 hours to obtain a pretreated injection mold;
[0074] S42: acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone were mixed in a weight ratio of 100:3:50:8:100, and coated on the surface of the pretreated injection mold at 30 mW / cm 2 After UV curing for 90 seconds, the base coating with a thickness of 500 μm was obtained by air drying at 60°C;
[0075] S43: 30 g of epoxy-terminated fluorinated polyurethane prepolymer, 70 g of epoxy resin E51, 38 g of curing agent, 10 g of defoaming agent, and 13 g of epoxy diluent were mixed and coated on the base coating, and cured at 120° C. for 2 h to obtain a surface coating with a thickness of 100 μm.
[0076] Comparative Example 1: 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane was used instead of tetraepoxysiloxane, and the other parameters were the same as those in Example 1.
[0077] Step 1:
[0078] Take 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and heat it to 85°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride and inhibitor p-hydroxyanisole, and add them dropwise to tetraepoxysiloxane, and control the mixture to be added dropwise within 30 minutes; after the addition, heat it to 100°C and react for 2 hours to obtain an acrylic modified resin; wherein 1,3-bis(N,N-diglycidylaminomethyl)cyclohexane and α-methylacrylic acid react at a molar ratio of epoxy group to carboxyl group of 2:1;
[0079] Step 2:
[0080] S21: Add boron nitride to isopropanol to obtain a suspension with a concentration of 3 g / L, ultrasonically oscillate at a power of 200 W for 24 hours, centrifuge at 3000 r / min for 10 minutes, take the upper suspension, centrifuge at 8000 r / min for 10 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride;
[0081] S22: 5 g of exfoliated boron nitride was dispersed in deionized water, and the pH was adjusted to 8 using tris(hydroxymethyl)aminomethane, 3 g of ethyl orthosilicate was added for hydrolysis for 6 h and then aged for 1 h, and 0.25 g of 3-mercaptopropyltrimethoxysilane was added; the mixture was stirred for reaction for 3 h and then filtered, and the filtrate was washed with deionized water and ethanol for 3 times respectively to obtain silica-modified boron nitride powder;
[0082] Step 3:
[0083] S31: perfluoropolyether diol and isophorone diisocyanate are mixed in a molar ratio of hydroxyl group to isocyanate group of 2:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70° C. for reaction for 2 h, and the mixture is cooled to obtain a polyurethane prepolymer;
[0084] S32: at 40°C, glycidol was added to the polyurethane prepolymer in a molar ratio of hydroxyl group to isocyanate group of 1:1, dibutyltin dilaurate was used as a catalyst, and the reaction was carried out at 70°C for 1 hour to obtain an epoxy-terminated fluorinated polyurethane prepolymer;
[0085] Step 4:
[0086] S41: Select an injection mold made of aluminum alloy, vertically cross-grind the surface of the injection mold with sandpaper for 5 minutes, clean the surface with clean water, and then soak the injection mold in a 0.2 mol / L hydrochloric acid solution and a 0.2 mol / L sodium hydroxide solution for 3 minutes in sequence; clean with acetone to remove surface impurities, mix silane coupling agent KH550, ethanol, and deionized water in a weight ratio of 20:72:8, and apply the mixture to the surface of the injection mold, and then dry at 100° C. for 1 hour to obtain a pretreated injection mold;
[0087] S42: acrylic modified resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone were mixed in a weight ratio of 100:3:50:3:100, and coated on the surface of the pretreated injection mold at 20 mW / cm 2 After UV curing for 30 seconds, the base coating with a thickness of 500 μm was obtained by air drying at 50°C;
[0088] S43: 20 g of epoxy-terminated fluorinated polyurethane prepolymer, 80 g of epoxy resin E51, 38 g of curing agent, 10 g of defoaming agent, and 13 g of epoxy diluent were mixed and coated on the base coating, and cured at 100° C. for 1 h to obtain a surface coating with a thickness of 100 μm.
[0089] Comparative Example 2: No surface coating was applied, and other parameters were the same as those in Example 2.
[0090] Step 1:
[0091] S11: Mix 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether in a molar ratio of 1:4, heat the system to 55°C, stir for 8 minutes, add KARSTEDT catalyst, stir until the temperature stabilizes, and continue the reaction for 4 hours to obtain tetraepoxysiloxane;
[0092] S12: Take tetraepoxysiloxane and heat it to 90°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride, and inhibitor p-hydroxyanisole, and add them dropwise to the tetraepoxysiloxane, and control the mixture to be added dropwise within 45 minutes; after the addition, heat it to 105°C and react for 2.5 hours to obtain an acrylic modified silicone resin; wherein the tetraepoxysiloxane and α-methylacrylic acid react at a molar ratio of epoxy group to carboxyl group of 2:1;
[0093] Step 2:
[0094] S21: Add boron nitride to isopropanol to obtain a suspension with a concentration of 3 g / L, ultrasonically oscillate at a power of 250 W for 24 hours, centrifuge at 3500 r / min for 13 minutes, take the upper suspension, centrifuge at 9000 r / min for 12 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride;
[0095] S22: 5 g of exfoliated boron nitride was dispersed in deionized water, and the pH was adjusted to 8.5 using tris(hydroxymethyl)aminomethane, 3 g of ethyl orthosilicate was added for hydrolysis for 6 h and then aged for 2 h, and 0.25 g of 3-mercaptopropyltrimethoxysilane was added; the mixture was stirred for reaction for 3.5 h and filtered, and the filtrate was washed with deionized water and ethanol for 3 times respectively to obtain silica-modified boron nitride powder;
[0096] Step 3:
[0097] S31: vertically cross-grinding the surface of the injection mold with sandpaper for 5 minutes, washing the surface with clean water, and then soaking the injection mold in a 0.2 mol / L hydrochloric acid solution and a 0.2 mol / L sodium hydroxide solution for 3 minutes in sequence; washing with acetone to remove surface impurities, mixing silane coupling agent KH550, ethanol, and deionized water in a weight ratio of 20:72:8 and applying the mixture to the surface of the injection mold, and then drying at 110° C. for 1.5 hours to obtain a pretreated injection mold;
[0098] S32: acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone were mixed in a weight ratio of 100:3:50:5:100, and coated on the surface of the pretreated injection mold at 25 mW / cm 2 After UV curing for 60 seconds, the film was dried by air blast at 55° C. to obtain a base coating with a thickness of 600 μm.
[0099] Comparative Example 3: The tetraepoxysiloxane and α-methyl acrylic acid in S12 were reacted in a molar ratio of epoxy group to carboxyl group of 1:1, and the other parameters were the same as those in Example 3.
[0100] Step 1:
[0101] S11: Mix 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether in a molar ratio of 1:4, heat the system to 60°C, stir for 10 minutes, add KARSTEDT catalyst, stir until the temperature stabilizes, and continue the reaction for 5 hours to obtain tetraepoxysiloxane;
[0102] S12: Take tetraepoxysiloxane and heat it to 95°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride, and inhibitor p-hydroxyanisole, and add them dropwise to the tetraepoxysiloxane, and control the mixture to be added dropwise within 60 minutes; after the addition, heat it to 110°C and react for 3 hours to obtain an acrylic modified silicone resin; wherein the tetraepoxysiloxane and α-methylacrylic acid react at a molar ratio of epoxy group to carboxyl group of 1:1;
[0103] Step 2:
[0104] S21: Add boron nitride to isopropanol to obtain a suspension with a concentration of 3 g / L, ultrasonically oscillate at a power of 300 W for 24 hours, centrifuge at 4000 r / min for 15 minutes, take the upper suspension, centrifuge at 10000 r / min for 15 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride;
[0105] S22: 5 g of exfoliated boron nitride was dispersed in deionized water, and the pH was adjusted to 8.5 using tris(hydroxymethyl)aminomethane, 3 g of ethyl orthosilicate was added for hydrolysis for 6 h and then aged for 3 h, and 0.25 g of 3-mercaptopropyltrimethoxysilane was added; the mixture was stirred for reaction for 4 h and then filtered, and the filtrate was washed with deionized water and ethanol for 3 times respectively to obtain silica-modified boron nitride powder;
[0106] Step 3:
[0107] S31: perfluoropolyether diol and isophorone diisocyanate are mixed in a molar ratio of hydroxyl group to isocyanate group of 2:1, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 80° C. for reaction for 4 hours, and the mixture is cooled to obtain a polyurethane prepolymer;
[0108] S32: adding glycidol to a polyurethane prepolymer at a molar ratio of hydroxyl group to isocyanate group of 1:1 at 50°C, using dibutyltin dilaurate as a catalyst, and reacting at 80°C for 2h to obtain an epoxy-terminated fluorinated polyurethane prepolymer;
[0109] Step 4:
[0110] S41: Select an injection mold made of aluminum alloy, vertically cross-grind the surface of the injection mold with sandpaper for 5 minutes, clean the surface with clean water, and then soak the injection mold in a 0.2 mol / L hydrochloric acid solution and a 0.2 mol / L sodium hydroxide solution for 3 minutes in sequence; clean with acetone to remove surface impurities, mix silane coupling agent KH550, ethanol, and deionized water in a weight ratio of 20:72:8, and apply the mixture to the surface of the injection mold, and then dry at 120° C. for 2 hours to obtain a pretreated injection mold;
[0111] S42: acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone were mixed in a weight ratio of 100:3:50:8:100, and coated on the surface of the pretreated injection mold at 30 mW / cm 2 After UV curing for 90 seconds, the base coating with a thickness of 500 μm was obtained by air drying at 60°C;
[0112] S43: 30 g of epoxy-terminated fluorinated polyurethane prepolymer, 70 g of epoxy resin E51, 38 g of curing agent, 10 g of defoaming agent, and 13 g of epoxy diluent were mixed and coated on the base coating, and cured at 120° C. for 2 h to obtain a surface coating with a thickness of 100 μm.
[0113] Experiment: According to the schemes in Examples 1 to 3 and Comparative Examples 1 to 3, the surface of an aluminum alloy (3A12) substrate with a size of 10 cm×10 cm×0.5 mm was pretreated and a wear-resistant coating was prepared, and then the performance of the coating was tested.
[0114] The test method is:
[0115] Friction resistance test: A friction tester is used to rub a random 3cm×3cm area on the sample surface. The friction probe is loaded with 200g. After 1000 frictions, a salt spray corrosion test is performed on the sample using a 5% sodium chloride saline solution. The test temperature is 50°C and the test time is 120h. The wear resistance of the coating is characterized by comparing the rust conditions of the substrate in the friction area and the non-friction area. If there is obvious rust in the friction area of the substrate relative to the non-friction area, it means that the coating has poor wear resistance. Otherwise, it has good wear resistance.
[0116] Impact resistance test: According to GB / T 1732-2020 "Determination of impact resistance of paint film", an impact test was carried out using an impact testing machine with a weight of 1kg. Each group of samples was tested 3 times. An electric spark leak detector was used to detect whether the samples had cracks. Finally, the impact resistance was evaluated based on the maximum stroke.
[0117] Surface hydrophilicity and hydrophobicity test: Use an optical contact angle meter to test the surface water contact angle.
[0118] The test results are shown in Table 1 below:
[0119] Table 1. Wear-resistant coating performance test results
[0120] project Wear resistance Impact height / cm Contact angle Example 1 No obvious rust in the friction area 61 122° Example 2 No obvious rust in the friction area 63 125° Example 3 No obvious rust in the friction area 64 127° Comparative Example 1 No obvious rust in the friction area 58 122° Comparative Example 2 Visible rust in the friction area 57 108° Comparative Example 3 Visible rust in the friction area 64 126°
[0121] Conclusion: The data of Examples 1 to 3 show that the coating prepared by the present invention has good performance. The data of Example 1 and Comparative Example 1 show that the base coating prepared by using siloxane can effectively improve the toughness of the coating, thereby improving the impact strength; the data of Example 2 and Comparative Example 2 show that the surface coating in Example 2 can improve the surface hydrophobicity, reduce the surface energy, and has high strength, and has a good protective effect on the substrate, while in Comparative Example 2, although the silicon-containing coating has good toughness, it has low strength, lacks the protection of the surface coating, and the wear resistance and impact strength are significantly reduced; the data of Example 3 and Comparative Example 3 show that the adhesion between the base coating and the substrate in Example 3 is good, and after thermal curing, it is cross-linked with the surface coating, and the coating protection effect is obvious, while in Comparative Example 3, the adhesion between the base coating and the substrate is poor, and it cannot be cross-linked with the surface coating, so after the friction test, the coating falls off, the substrate lacks the protection of the coating, and rust occurs in the salt spray test.
[0122] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing an injection mold modified with a wear-resistant coating, characterized in that: The following steps are involved: Step 1: An aluminum alloy injection mold is selected, and the surface of the injection mold is vertically cross-grinded for 5 minutes with sandpaper, and the surface is cleaned with clean water, and then the injection mold is soaked in hydrochloric acid solution and sodium hydroxide solution in turn for 3 to 5 minutes; acetone is used to clean and remove surface impurities, and a mixture of silane coupling agent KH550, ethanol, and deionized water is applied to the surface of the injection mold, and then dried at 100 to 120°C for 1 to 2 hours to obtain a pretreated injection mold; Step 2: Mix acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder and acetone, and apply it on the surface of the pre-treated injection mold at 20-30 mW / cm 2 After UV curing for 30 to 90 seconds, the coating is dried by air blast at 50 to 60° C. to obtain a base coating with a thickness of 300 to 500 μm; Step 3: The epoxy-terminated fluorinated polyurethane prepolymer, epoxy resin E51, curing agent, defoaming agent and epoxy diluent are mixed and coated on the base coating, and cured at 100-120° C. for 1-2 hours to obtain a surface coating with a thickness of 100-200 μm.
2. The process for preparing a wear-resistant coating modified injection mold according to claim 1, characterized in that: In step 1, the concentration of the hydrochloric acid solution is 0.2-0.25 mol / L; the concentration of the sodium hydroxide solution is 0.2-0.25 mol / L; the weight ratio of the silane coupling agent KH550, ethanol, and deionized water is 20:(70-75):(5-10).
3. The process for preparing a wear-resistant coating modified injection mold according to claim 1, characterized in that: In step 2, acrylic modified silicone resin, photoinitiator, curing agent, silica modified boron nitride powder, and acetone are mixed in a weight ratio of (100-120):(3-5):(46-54):(3-8):
100.
4. The process for preparing a wear-resistant coating modified injection mold according to claim 1, characterized in that: In step 2, the method for preparing the acrylic acid-modified silicone-containing resin comprises the following steps: Take 2,4,6,8-tetramethylcyclotetrasiloxane and allyl glycidyl ether, mix them, heat them until the temperature in the system reaches 50-60°C, stir them for 5-10 minutes, then add KARSTEDT catalyst, stir them until the temperature is stable, and continue to react for 3-5 hours to obtain tetraepoxysiloxane; take tetraepoxysiloxane and heat it to 85-95°C, mix α-methylacrylic acid, catalyst benzyltriethylammonium chloride and inhibitor p-hydroxyanisole, and add them dropwise to the tetraepoxysiloxane, and control the mixture to be added dropwise within 30-60 minutes; after the addition is completed, heat it to 100-110°C and react for 2-3 hours to obtain acrylic modified silicone resin.
5. The process for preparing a wear-resistant coating modified injection mold according to claim 4, characterized in that: 2,4,6,8-Tetramethylcyclotetrasiloxane and allyl glycidyl ether react at a molar ratio of 1:4; tetraepoxysiloxane and α-methacrylic acid react at a molar ratio of epoxy group to carboxyl group of 2:
1.
6. The process for preparing a wear-resistant coating modified injection mold according to claim 1, characterized in that: In step 2, the method for preparing silicon dioxide-modified boron nitride powder comprises the following steps: S1: Add boron nitride to isopropanol to obtain a suspension with a concentration of 1-3 g / L, ultrasonically oscillate at a power of 200-300 W for 24 hours, centrifuge at 3000-4000 r / min for 10-15 minutes, take the upper suspension, centrifuge at 8000-10000 r / min for 10-15 minutes, take the upper clear liquid, and air-dry to obtain exfoliated boron nitride; S2: Take 3-5 parts of exfoliated boron nitride by weight and disperse them in deionized water, use trishydroxymethylaminomethane to adjust the pH to 8-8.5, add 2.5-3 parts of ethyl orthosilicate to hydrolyze for 6 hours and then age for 1-2 hours, add 0.2-0.28 parts of 3-mercaptopropyltrimethoxysilane; stir the reaction for 3-4 hours and filter, take the filtrate and wash it with deionized water and ethanol for 3-5 times respectively to obtain silica-modified boron nitride powder.
7. The process for preparing a wear-resistant coating modified injection mold according to claim 1, characterized in that: In step 3, the amount of each component used, by weight, is 20 to 30 parts of epoxy-terminated fluorine-containing polyurethane prepolymer, 70 to 80 parts of epoxy resin E51, 35 to 40 parts of curing agent, 8 to 13 parts of defoaming agent, and 10 to 15 parts of epoxy diluent.
8. The process for preparing a wear-resistant coating modified injection mold according to claim 1, characterized in that: In step 3, the method for preparing the epoxy-terminated fluorinated polyurethane prepolymer comprises the following steps: Perfluoropolyether diol and isophorone diisocyanate are mixed, dibutyltin dilaurate is used as a catalyst, the temperature is raised to 70-80°C for reaction for 2-4 hours, and the polyurethane prepolymer is obtained by cooling; glycidol is added to the polyurethane prepolymer at 40-50°C, dibutyltin dilaurate is used as a catalyst, and the reaction is carried out at 70-80°C for 1-2 hours to obtain an epoxy-terminated fluorine-containing polyurethane prepolymer.
9. The process for preparing a wear-resistant coating modified injection mold according to claim 8, characterized in that: Perfluoropolyether diol and isophorone diisocyanate are mixed at a molar ratio of 2:1 between hydroxyl group and isocyanate group; and glycidol is added to the polyurethane prepolymer at a molar ratio of 1:1 between hydroxyl group and isocyanate group.
10. The injection mold prepared by the preparation process according to any one of claims 1 to 9.
Citation Information
Patent Citations
Epoxy polyhedralsilsesquioxane modified epoxy resin-based heat conduction insulating coating and preparation method thereof
CN106995641A
Coating material for coating layer of injection mold and method of manufacturing coating layer of injection mold
CN110713764A
Boron nitride nanosheet in-situ loaded nano silicon oxide hybrid filler and preparation method thereof, and rubber composite material
CN111171382A
Injection mold with high-hardness wear-resistant coating and preparation method of injection mold
CN117165128A
1, 3, 5, 7-tetramethyl tetraglycidyl propoxy ether cyclotetrasiloxane as well as preparation method and application thereof
CN117534701A
Cited By
A nano-ceramic reinforced composite wear resistant coating for injection mold surfaces and a method of making the same
CN122832585A